THE RELATIONSHIP BETWEEN DOUBLE BURDEN AND WORK FATIGUE IN FEMALE LECTURERS AND STAFFS AT FACULTY OF HEALTH SCIENCE UPNVJ IN 2020 - Shafira, Nadia Rizki (Universitas Pembangunan Nasional Veteran Jakarta, 2020)
Fatigue is one of Occupational Health and Safety problems which can cause work accidents. Some factors that can affect fatigue such as work factors (double burden, work shift, work duration, work term and rest duration) individual factors (age, gender, nutritional status, health status and psychological condition) and environmental factors that will impact on decreasing productivity, quality of work and loss of working hours. The purpose of this study was to analyze the relationship between double burden and work fatigue in female lecturers and staffs in health science faculty of UPNVJ. This study was analytic quantitative research with a cross-sectional design. A total of 53 workers were recruited as samples by using a purposive sampling technique. The information was gathered through questionnaires Subjective Self Rating Test from Industrial Fatigue Research Comitte (IFRC) Jepang and questionnaires of double burden. Data were analyzed by using a Chi-Square Test with a confidence level of 0,05. The results of this study indicate that 40 of 53 workers (75,5%) feel high fatigued. Variables associated with fatigue are double burden (p = 0.0001), work term (p = 0.0001) and age (p = 0.022). It is recommended for workers to increase the consumption of water and properly use the time for family as well as possible.Keywords: Fatigue, Double Burden, Female Worker